implicit method by three pont backward method

2 vues (au cours des 30 derniers jours)
Faraz Vossoughian
Faraz Vossoughian le 14 Avr 2020
Modifié(e) : darova le 26 Avr 2020
Hi im trying to code the following implicit method 3 point backward method, but im not gettingt the right answer for y. Can someone help please.The function contains the method, so i believe theres something wrong there.
% problem 2-2 (3PBDF)
x0=0;
xmax=1;
h=0.01*.25;
a=1;
y0=1;
[xs,y]=ThreePointBDF(x0, xmax, h, a, y0);
plot(xs,y)
clear all
close all
f= @(x,y) -y;
x(1)=0;
y(1)=1;
n=10;% number of iterations
h=(1-0)/n; %stepsize h =(b-a)/n)
for i=1:n
y(i+1)=y(i)+h*f(x(i),y(i));
x(i+1)=i*h;
end
x=x(:)
y=y(:)
plot(x,y)
xlabel('x')
ylabel('y')
function [xs,y] = ThreePointBDF(x0, xmax, h, a, y0)
% This function should return the numerical solution of y at x = xmax.
% (It should not return the entire time history of y.)
% TO BE COMPLETED
f=@(x,y) -a*y;
xs=x0:h:xmax;
y=zeros(1,length(xs));
y(1)=y0;
y(2)=y0+h*f(x0,y0);
for i=1:length(xs)-1
disp(i)
y(i+1)=(4/3*y(i+1)-1/3*y(i))+2*h/3*f(xs(i+1),y(i+1));
end
end
  2 commentaires
darova
darova le 14 Avr 2020
I don't understand it
I only know something like this
y(i+1) = y(i) + h*f(x(i),y(i));
Maybe in your case this should be
y1 = y(i) + h*f(x(i),y(i));
y(i+1) = 4/3*y(i)-1/3*y(i-1)+2/3*h*f(x(i+1),y1);
Madmiller
Madmiller le 26 Avr 2020
Modifié(e) : darova le 26 Avr 2020
I agree. Can you explain more? Im interested too

Connectez-vous pour commenter.

Réponses (0)

Catégories

En savoir plus sur Loops and Conditional Statements dans Help Center et File Exchange

Produits

Community Treasure Hunt

Find the treasures in MATLAB Central and discover how the community can help you!

Start Hunting!

Translated by